Dissolved cobalt speciation and reactivity in the eastern tropical North Atlantic - Baars, Oliver; Croot, Peter (Marine Chemistry, 2015)
Recent studies highlight the role of cobalt (Co) as an important micro-nutrient with a complex scavenged type oceanic distribution. To better understand the biogeochemical cycle of Co we investigate the distribution, speciation and reactivity of dissolved Co in the eastern tropical North Atlantic in the upper 800 m of the water column. For this purpose, we complement classical Co ligand titrations that require a thermodynamic equilibrium with evaluations of ligand-exchange kinetics and reducibility of potential Co(III) species. The experiments include additions of the artificial Co binding ligands dimethylglyoxime or Nioxime and detection by cathodic stripping voltammetry. We find two pools of Co compounds: a labile fraction that exchanges Co within minutes and a strong/inert fraction that does not react within a 24-h period. No intermediate, slowly exchanging fraction is observed. Detection window experiments to determine complex stability constants show that the labile Co fraction is weak and likely consists of Co(II) complexes with no detectable free Co(II) ligands. The fraction of inert Co is always highest at the depth of the chlorophyll-a maximum. Addition of the reductant ascorbate increases the fraction of Co with rapid ligand-exchange kinetics and indicates the presence of dissolved reducible Co(III). The apparent Co(III) reducibility is highest at the chlorophyll-a maximum and decreases in deeper waters. Our results are in agreement with a possible release of Co(III) species, including vitamin B12, by phytoplankton and associated bacteria. The presented results have important implications for our understanding of the biological availability and the marine cycle of Co.